Public Sentiment and Attribution of Responsibility toward Public Institutions in the LPDP Alumni Controversy on Social Media - Haura Balqis; Fitria Ayuningtyas (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines public sentiment and responsibility attribution toward LPDP as a public institution in a social media controversy involving one of its alumni. Drawing on Attribution Theory and digital crisis communication, this study argues that reputational risk is shaped not only by negative sentiment but also by how public responsibility is attributed to individuals and institutions. A descriptive quantitative approach was applied using computational sentiment analysis and text-based attribution analysis. Data were collected from Twitter/X through scraping with the keyword “LPDP Dwisasetyaningtyas” during 20 February–6 March 2026”. A total of 106 tweets were processed using the Knowledge Discovery in Databases (KDD) stages: data selection, preprocessing, transformation, analysis, and interpretation. The results show that neutral sentiment dominated the conversation at 82.08%, followed by negative sentiment at 15.09% and positive sentiment at 2.83%. Attribution analysis shows that individual attribution appeared in 100% of tweets, institutional attribution in 89.62%, moral attribution in 61.32%, and systemic attribution in 10.38%. These findings indicate that the LPDP controversy is better understood as a reputational issue based on visibility and attribution rather than merely a crisis driven by negative sentiment.